PENGARUH MEDIA GOOGLE FORM DALAM MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA MATERI ASAM BASA - Rizky Handayani; Usman Sain; Mukhamad Nurhadi (Orbital: Jurnal Pendidikan Kimia, 2021)
The aim of research was found the effect of google form media on problem-based learning models with student learning outcomes of XI at one of the schools in Samarinda in acid-base chapter. Design of research was used is true-experimental design is especially posttest only control design. The population was all students of class XI MIPA which amounted to 105 students. The research subject was taken by cluster random sampling. Data collection techniques in this research are test, documentation, and observation techniques. The test technique was obtained of three time post-test at the end of each meeting were obtained from 20% of each post-test score and 40% of final examination score. The documentation data as previous student learning outcomes was used to determine homogeneous of the sample. The observation data was obtained of direct observation of the implementation of the steps of teacher and student learning. Technical analysis of the data using normality test, F-test, and T-test. The average of experimental class learning outcomes and the control class learning outcomes were 79.86 and 73.21, respectively. The T-test result shown T-count (2.75)> T-table (1.67) with significant 0.05. So it can be concluded that the google form media give effect in problem-based learning models onto student learning outcomes in acid-base chapter.